STRATEGI KEPALA SEKOLAH PEREMPUAN DALAM MENINGKATKAN MUTU PENDIDIKAN - Wulandari, Yeni; Dwi Sartika, Eva; Perawati, Perawati (Graduate Program Magister Manajemen Pendidikan, 2018)
This studyÂ aimedÂ at describing the leadership strategy of Â women principal.Â This researchÂ was doneÂ in SDÂ NegeriÂ Kota PalembangÂ 116. The approach usedÂ in this researchÂ was aÂ case study.Â Results of the studyÂ in improvingÂ the quality of educationÂ in SD Negeri 116Â PalembangÂ includeÂ a good personal approach with all stakeholders of the school; planning the school with the greatest extent possible, analyze the challenges, barriers and opportunities in the future; establish good cooperationÂ with allÂ educators, empowering educational effort through cooperation, provide an opportunityÂ toÂ improveÂ educatorsâ practices, and encourage the involvement ofÂ the educatorsÂ onÂ supporting theÂ programsÂ of the school. The results implied the teachersÂ Â to maximizeÂ the existingÂ facilities and infrastructureÂ to maximizeÂ the learningÂ Â process,Â and Â the schoolÂ has hadÂ a strongÂ culture.